Organic Contaminants in Crosslinked Polyethylene for Demanding High Voltage Applications - Doedens, Espen (My University, 2012)
Oxidation or chemical aging of polyethylene may occur before, during or even after the extrusion process used to produce crosslinked polyethylene (XLPE), creating oxidized particles referred to as organic contaminants. XLPE is a common insulating material used for e.g. high voltage cables. Not much work is published on the effect of organic contaminants on electrical degradation such as electrical treeing and water treeing. This work aims to examine the effects of organic contaminants with different degrees of oxidation on in particular electrical treeing. These contaminants were introduced in XLPE samples made for electrical treeing measurements. Instead of using a commonly used needle-needle or needle-plane configuration, a wire-plane configuration was used for all test samples. The electrical tree initiation and propagation was examined with a method developed at Chalmers University of Technology. As found in the literature, the organic contaminants are known to have increasing conductivity and permittivity depending on the degree of oxidation. These properties could create local field enhancements in the material. Also the morphology of the material might be affected when contaminants are inserted. A combination of these factors might influence the electrical performance of the insulation. As this was the first time organic contaminants were introduced into the wire-plane test method, a wide variety of tests were performed such as wet and dry aging, AC tests and DC tests. From these tests a number of observations were made, giving support to a set of possible conclusions for these topics.
Keywords: Energi; Materialvetenskap; Elkraftteknik; Energy; Materials Science; Electric power engineering